Group B Streptococcal Septicaemia Causing Bilateral Acute Parotitis in an Infant: A Rare Case Report - Sumaira Wajid; Wajid Hussain (Liaquat National Journal of Primary Care)
Acute parotitis is a rare condition in young infants and is characterized by swelling of the parotid gland associated with fever and pain. Staphylococcus aureus is the most common causative agent of this disease. Prevalence is higher in males. We describe the case of a 55-day-old Asian female infant who presented in the emergency department with complaints of fever, reluctance to feed, and irritability with unremarkable examination. During hospitalization pre-auricular edema was observed bilaterally close to the angle of the jaw along with signs of inflammation, greater on the right side. Ultrasound findings showed parotid gland enlargement and blood culture report was positive for Streptococcus pyogenes. Antibiotic treatment with injectable Vancomycin was given for 7 days and the patient had rapid recovery in terms of both symptom improvement and reduction of glandular swelling. This case illustrates the need for consideration of this disease in infants and its likelihood in both genders and emphasizes the early institution of appropriate therapy of acute parotitis for faster recovery and prevention of complications. There is much data on acute parotitis in adolescents but due to the paucity of data in young infants, there is a need to investigate further the causes and treatment of this disease in infants.